ADVERSE SELECTION IN BID ASK SPREAD FOR INDONESIAN BLUE CHIP STOCKS - Daulat H.H. Pohan; Angelia Josephine (ESENSI: Jurnal Manajemen Bisnis, 2018)
The objectives of this study were to observe the relationship among adverse selection, corporate governance, and ownership pattern in Indonesia. There are several conclusions that can be taken from the result. First, adverse selection exists in Indonesian companies. Second, corporate governance may not affect adverse selection. Third, the pattern of ownership may not affect adverse selection. These conclusions show that it is wiser for investors not to use only corporate governance or ownership pattern for investment decisions in Indonesia.